Science, technology and innovation capability gaps, policy environment and evolving policy tools for sustainable development (UN New YorkUS, 2014)
Discusses the importance of an enabling environment for innovation in developing countries, presents the main capability gaps identified in these countries, and describes some features of the policy environment in which developing countries need to address their STI challenges. Examines a number of developments in the area of STI policy toos. Concludes by presenting some sugestions about issues that can be addressed by participating experts.
Note by the UNCTAD Secretariat.